2022
DOI: 10.3390/ani12182410
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analyses Provide Insights into the Auditory Function in Trachemys scripta elegans

Abstract: An auditory ability is essential for communication in vertebrates, and considerable attention has been paid to auditory sensitivity in mammals, birds, and frogs. Turtles were thought to be deaf for a long time; however, recent studies have confirmed the presence of an auditory ability in Trachemys scripta elegans as well as sex-related differences in hearing sensitivity. Earlier studies mainly focused on the morphological and physiological functions of the hearing organ in turtles; thus, the gene expression pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…scripta elegans [ 42 ]. Further comparative transcriptomics analysis results showed that six DEGs ( GABRA1 , GABRG2 , GABBR2 , GNAO1 , SLC38A1 , and SLC12A5 ) in the GABAergic synapse pathway were identified to explain the differences in sexually dimorphic hearing sensitivity [ 43 ]. In our study, our experimental animals were six 2-year-old healthy T .…”
Section: Discussionmentioning
confidence: 99%
“…scripta elegans [ 42 ]. Further comparative transcriptomics analysis results showed that six DEGs ( GABRA1 , GABRG2 , GABBR2 , GNAO1 , SLC38A1 , and SLC12A5 ) in the GABAergic synapse pathway were identified to explain the differences in sexually dimorphic hearing sensitivity [ 43 ]. In our study, our experimental animals were six 2-year-old healthy T .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that during the transmission of acoustic signals to the neural centers of the brain, presynaptic cells can achieve rapid excitatory inhibition through the release of GABA to balance neural excitation generated by glutamate and ultimately reduce the sensitivity of the auditory response [32]. Lu et al [33] conducted transcriptome studies using the inner ear of turtles and found that male turtles' auditory sensitivity was weaker than that of female turtles, possibly because multiple genes involved in the GABAergic synaptic pathway were significantly up-regulated in male turtles, and thus activation of this pathway slowed down the auditory response speed of the nerve center. Yang et al [34] identified several highly expressed hearing-related genes in the swim bladder tissue of channel catfish, which were significantly enriched for the glutamatergic synaptic pathway and GABAergic synaptic pathway.…”
Section: Hearing Differences Of Yangtze Finless Porpoises In Differen...mentioning
confidence: 99%